2018
DOI: 10.1002/ange.201711780
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Dearomatization Strategy for an Expedient Biomimetic Route to the Bielschowskysin Skeleton

Abstract: Bielschowskysin (1), the flagship of the furanocembranoid diterpene family,has attracted attention from chemists owingtoits intriguing and daunting polycyclic architecture and medicinal potential against lung cancer.T he high level of functionalization of 1 poses ac onsiderable challenge to synthesis.H erein, as tereoselective furan dearomatization strategy of furanocembranoids was achieved via the intermediacy of chlorohydrins.T he stereochemical course of the kinetic dearomatization was established, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The contents were cooled using ice bath, and then, iodine (3.17 g, 24.97 mmol, 1.2 equiv) as a solid was added in one portion and slowly warmed to room temperature over 10–15 min. Alcohol 3 (6 g, 20.81 mmol, 1.0 equiv) in CH 2 Cl 2 (10 mL) was added, and the reaction mixture was stirred for 1 h at room temperature for the completion of reaction. The reaction volume was reduced approximately to 50 mL using the rotary evaporator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contents were cooled using ice bath, and then, iodine (3.17 g, 24.97 mmol, 1.2 equiv) as a solid was added in one portion and slowly warmed to room temperature over 10–15 min. Alcohol 3 (6 g, 20.81 mmol, 1.0 equiv) in CH 2 Cl 2 (10 mL) was added, and the reaction mixture was stirred for 1 h at room temperature for the completion of reaction. The reaction volume was reduced approximately to 50 mL using the rotary evaporator.…”
Section: Methodsmentioning
confidence: 99%
“…To date, a series of model studies to bielschowskysin 1 have been reported (Figure ). Sulikowski and our group independently reported the synthesis of the bicyclo[3.2.0]­heptane core based on a biomimetic transannular [2 + 2] photocycloaddition to construct the cyclobutane ring (Figure a,b, respectively). , Nicolaou et al reported an expedient synthesis of the first 14-carbon framework of 1 through RCM and transannular [2 + 2] studies (Figure c) . Mulzer and co-workers disclosed a nonphotochemical strategy to the bicyclo[3.2.0]­heptane core structure of bielschowskysin, featuring the all-carbon quaternary center at C12 for the first time (Figure d) .…”
Section: Introductionmentioning
confidence: 99%
“…10c Synthetic chemists have made efforts towards the synthesis of the cyclobutane-centered scaffold in recent years. 10 To date, only Roche’s group 15a b and Nicolaou’s group 15c have successfully built the core tricyclo-[9.3.0.0]-tetradecane skeleton found in bielschowskysin ( 10 ).…”
Section: Computational Studies On the Biomimetic Synthesis Of Bielsch...mentioning
confidence: 99%